External injuries, trauma and avoidable deaths in Agincourt, South Africa: a retrospective observational and qualitative study. Issue 6 (4th June 2019) - Edem, Idara J; Dare, Anna J; Byass, Peter; D'Ambruoso, Lucia; Kahn, Kathleen; Leather, Andy J M; Tollman, Stephen; Whitaker, John; Davies, Justine
Abstract : Objective: Injury burden is highest in low-income and middle-income countries. To reduce avoidable deaths, it is necessary to identify health system deficiencies preventing timely, quality care. We developed criteria to use verbal autopsy (VA) data to identify avoidable deaths and associated health system deficiencies. Setting: Agincourt, a rural Bushbuckridge municipality, Mpumalanga Province, South Africa. Participants: Agincourt Health and Socio-Demographic Surveillance System and healthcare providers (HCPs) from local hospitals. Methods: A literature review to explore definitions of avoidable deaths after trauma and barriers to access to care using the 'three delays framework' (seeking, reaching and receiving care) was performed. Based on these definitions, this study developed criteria, applicable for use with VA data, for identifying avoidable death and which of the three delays contributed to avoidable deaths. These criteria were then applied retrospectively to the VA-defined category external injury deaths (EIDs—a subset of which are trauma deaths) from 2012 to 2015. The findings were validated by external expert review. Key informant interviews (KIIs) with HCPs were performed to further explore delays to care. Results: Using VA data, avoidable death was defined with a focus on survivability, using level of consciousness at the scene and ability to seek care as indicators. Of 260 EIDs (189 trauma deaths), there were 104 (40%) avoidable EIDs and 78 (30%) avoidable trauma deaths (41% of trauma deaths). Delay in receiving care was the largest contributor to avoidable EIDs (61%) and trauma deaths (59%), followed by delay in seeking care (24% and 23%) and in reaching care (15% and 18%). KIIs revealed context-specific factors contributing to the third delay, including difficult referral systems. Conclusions: A substantial proportion of EIDs and trauma deaths were avoidable, mainly occurring due to facility-based delays in care. Interventions, including strengthening referral networks, may substantially reduce trauma deaths.